Increased nutrients from aeolian-dust and riverine origin decrease the CO2-sink capacity of coastal South Atlantic waters under UVR exposure - Cabrerizo, Marco J.; Carrillo, Presentación; Villafañe, Virginia Estela; Medina Sánchez, Juan Manuel; Helbling, Eduardo Walter (Limnology and Oceanography)
Increases in ultraviolet radiation (UVR) levels due to the ongoing stratification of water bodies and higher nutrient concentrations either through riverine or aeolian-dust-inputs are expected in the near future in coastal surface waters. Here, we combined remote-sensing data of particulate organic carbon (POC; 1997–2016 period), observational data of solar radiation (1999–2015 period), and a mid-term experimental approach with coastal plankton communities from South Atlantic Ocean (SAO) to test how the interaction between increased nutrients by riverine and aeolian-dust inputs and high UVR may alter the community dynamics and the CO2 sink capacity of these ecosystems in the future. Our results show a decline ∼ 27% in the sink capacity of the coastal ecosystems regardless of the nutrient source considered and under high UVR levels. This decreased CO2 uptake was coupled with a high dynamic photoinhibition and dark recovery of photosystem II and shifts in the community structure toward the dominance by nano-flagellates. Moreover, remote-sensing data also evidences an incipient tipping point with decreasing POC values in this area over the annual planktonic succession. Therefore, we propose that to continue this climate and human-mediated pressure, these metabolic responses could be strengthened and extended to other productive coastal areas. Fil: Cabrerizo, Marco J. Universidad de Granada; España. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina Fil: Carrillo, Presentación. Universidad de Granada; España Fil: Villafañe, Virginia Estela. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Medina Sánchez, Juan Manuel. Universidad de Granada; España Fil: Helbling, Eduardo Walter. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina